Simulations and Experiments Toward Continuous Wave 167 nm Laser Generation for ARPES With High Energy Resolution - Zhang, Ziyue; Han, Hainian; Zhao, Guodong; Liu, Guodong; Zhou, Xingjiang; Wei, Zhiyi (Frontiers in Physics, 2022)
Continuous wave (CW) laser at vacuum ultraviolet (VUV) range with narrow linewidth is an ideal optical source in Angle-resolved-photoemission-spectroscopy (ARPES) for the research of superconductors with narrow bandgap. In this paper we present an eighth-harmonic-generation (EHG) laser scheme for CW laser generation at the VUV range, in particular at 167.75 nm, based on the cascaded power enhancement cavities. An intracavity second harmonic generation (ICSHG) 671 nm laser with narrow linewidth and active frequency stabilization is built as the first stage, delivering 2.55 W output power. A resonant cavity for fourth-harmonic-generation (FHG) constitutes the second stage, which generates the 335.5 nm laser with the output power of up to 1.25 W. The third stage is designed for the EHG of 167.75 nm based on the KBBF crystal. To realize the efficient CW laser generation at 167.75 nm, a theoretical analysis concerning enhancement factor and the conversion efficiency of the KBBF based EHG is carried out. The results shows that it is possible for mW-level 167.75 nm generation if the transmittance of the KBBF prism coupled device is increased to 97%. A 59 W circular intracavity power is observed in the 335.5 nm enhanced cavity experiments, corresponding to the peak power density of up to 20.86 MW/cm2. This work paves a solid way for CW VUV laser generation with narrow linewidth, which would be an ideal tool for the extremely high resolution ARPES.